Association of net pterygium tissue mass (dryweight) in determining changes in oculovisual functions and anterior corneal curvature relative to pterygium types - Che Rosli, Noor Syahira (2020)
Introduction: Dryweight in pterygium is more towards the fleshy appearance of the fibrous tissue. Aim: The goal of this study was to determine the predictive ability of net pterygium tissue mass (dryweight) on predicting changes in anterior corneal cur-vature and oculovisual functions relative to pterygium types. Methodology: A total of 93 primary pterygium patients who visited an ophthalmology clinic were selected as participants. The net pterygium tissue mass were obtained via freeze dry method sub-sequent to pterygium excision using fibrin glue adhesive method. Best corrected visu-al acuity (BCVA) and contrast sensitivity function (CSF) were measured by using M&S Smart System II as measurement for oculovisual function, while the changes of ante-rior corneal curvature was measured using corneal topography. Results: The mean and standard deviation for BCVA, CSF and SimK were 0.44 ± 0.30 LogMAR, 24.28 ± 17.66 % and 4.64 ± 4.18 D respectively. This study found that the predictive ability of pterygium dryweight with BCVA were strong in Type I and Type III while moderate in Type II with 13.10% (R2 = 0.131, p < 0.05) in Type I. Slight increase trend were noted in both Type II with 53% (R2 = 0.530, p < 0.05) and Type III, with 21.60% (R2 = 0.216, p < 0.05). For CSF, the predictive ability of pterygium dryweight were strong in all types with Type I, Type II and III reported 21.6% (R2 = 0.216, p < 0.05), 31.8% (R2 = 0.318, p < 0.05), 28.9% (R2 = 0.289, p < 0.05) respectively. The predictive ability of pterygium dry-weight for SimK were strong in all types with contribution of 44.7% (R2 = 0.447, p < 0.05), 47.7% (R2 = 0.477, p < 0.05), 39.1% (R2 = 0.391, p < 0.05) respectively. Conclusion: Net pterygium tissue mass (dryweight) is a strong factor in predicting changes of ocu-lovisual functions and anterior corneal curvature in relation to pterygium types.